2010
DOI: 10.4314/wsa.v36i4.58419
|View full text |Cite
|
Sign up to set email alerts
|

The effect of conditioning with NaCl, KCl and HCl on the performance of natural clinoptilolite’s removal efficiency of Cu<sup>2+</sup> and Co<sup>2+</sup> from Co/Cu synthetic solutions

Abstract: Southern African clinoptilolite's capability as an ion-exchanger with respect to Cu 2+ and Co 2+ was investigated in order to consider its viability in the removal of metal cations from aqueous solutions. The effect of chemical conditioning was investigated using sodium chloride (NaCl), hydrochloric acid (HCl) and potassium chloride (KCl). The most efficient activating or conditioning reagent was found to be HCl at 0.02 M concentration, followed by KCl at 0.04 M and then NaCl at 0.04 M. The worst performing cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
9
0
2
Order By: Relevance
“…However, other authors like Mamba et al . studied the effect of treating the clinoptilolite with NaCl, KCl, and HCl to remove Cu and Co and the best results were reached by the zeolite treated with HCl 0.02 M followed by the zeolite treated with NaCl 0.04 M. The same authors, in a previous work, studied the removal of copper and cobalt using clinoptilolite modified with different concentration of HCl (0.02; and 0.04 M) . The zeolite modified with the lowest HCl concentration was the best for Co and Cu removal.…”
Section: Resultsmentioning
confidence: 99%
“…However, other authors like Mamba et al . studied the effect of treating the clinoptilolite with NaCl, KCl, and HCl to remove Cu and Co and the best results were reached by the zeolite treated with HCl 0.02 M followed by the zeolite treated with NaCl 0.04 M. The same authors, in a previous work, studied the removal of copper and cobalt using clinoptilolite modified with different concentration of HCl (0.02; and 0.04 M) . The zeolite modified with the lowest HCl concentration was the best for Co and Cu removal.…”
Section: Resultsmentioning
confidence: 99%
“…In the paper by Kraljević Pavelić et al (2017) , it was specifically shown that different micronization methods change the clinoptilolite tuff properties by affecting the surface area, pore size, and silicon to aluminum ratio on the surface of the material. Moreover, hydrochloric acid (HCl) that is also present in the stomach may change clinoptilolite physical chemical properties and has been proven to enhance the clinoptilolite ion-exchange capacity for Cu 2+ and Co 2+ in a synthetic Cu-Co solution at concentrations relevant for the stomach in vivo (0.1 M) ( MambaI et al, 2010 ). Still, the clinoptilolite ion-exchange effects in vivo are complex and cannot be linearly explained as they are not affected only by the environmental conditions (pH, temperature, etc.)…”
Section: Zeolites Effects On Oxidative Stress and Immune Systemmentioning
confidence: 99%
“…For instance, the hydrochloric acid in the stomach (low pH) and bile salts in the intestine (high pH) may change the physiochemical properties of mineral adsorbents thereby enhancing their ion-exchange capacity. This process may lead to the release of minerals from the surface of the adsorbents into the surrounding milieu, thus increasing the concentration of minerals (in addition to mineral content of feed) in the systemic circulation and subsequent accumulation in the body (Park et al 2002;Mascolo et al 2004;MambaI et al 2010). Also, the ion-exchange process, particularly for adsorbents with a high CEC, may lead to adsorption of minerals and nutrients from feed, resulting in the deficiencies of micronutrients such as iron, potassium, and vitamins in farm animals (Ralla et al 2010).…”
Section: Micronutrientsmentioning
confidence: 99%